Dampening effects of long-term experimental drought on growth and mortality rates of a Holm oak forest - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (GLOBAL CHANGE BIOLOGY, 2013)
Forests respond to increasing intensities and frequencies of drought by reducing growth and with higher tree mortality rates. Little is known, however, about the long-term consequences of generally drier conditions and more frequent extreme droughts. A Holm oak forest was exposed to experimental rainfall manipulation for 13years to study the effect of increasing drought on growth and mortality of the dominant species Quercus ilex, Phillyrea latifolia, and Arbutus unedo. The drought treatment reduced stem growth of A. unedo (-66.5%) and Q. ilex (-17.5%), whereas P. latifolia remained unaffected. Higher stem mortality rates were noticeable in Q. ilex (+42.3%), but not in the other two species. Stem growth was a function of the drought index of early spring in the three species. Stem mortality rates depended on the drought index of winter and spring for Q. ilex and in spring and summer for P. latifolia, but showed no relation to climate in A. unedo. Following a long and intense drought (2005-2006), stem growth of Q. ilex and P. latifolia increased, whereas it decreased in A. unedo. Q. ilex also enhanced its survival after this period. Furthermore, the effect of drought treatment on stem growth in Q. ilex and A. unedo was attenuated as the study progressed. These results highlight the different vulnerabilities of Mediterranean species to more frequent and intense droughts, which may lead to partial species substitution and changes in forest structure and thus in carbon uptake. The response to drought, however, changed over time. Decreased intra- and interspecific competition after extreme events with high mortality, together with probable morphological and physiological acclimation to drought during the study period, may, at least in the short term, buffer forests against drier conditions. The long-term effects of drought consequently deserve more attention, because the ecosystemic responses are unlikely to be stable over time.Nontechnical summaryIn this study, we evaluate the effect of long-term (13years) experimental drought on growth and mortality rates of three forest Mediterranean species, and their response to the different intensities and durations of natural drought. We provide evidence for species-specific responses to drought, what may eventually lead to a partial community shift favoring the more drought-resistant species. However, we also report a dampening of the treatment effect on the two drought-sensitive species, which may indicate a potential adaptation to drier conditions at the ecosystem or population level. These results are thus relevant to account for the stabilizing processes that would alter the initial response of ecosystem to drought through changes in plant physiology, morphology, and demography compensation.
Keywords: acclimation; Arbutus unedo; experimental drought; global-change-type drought; Holm oak; mediterranean forest; phillyrea latifolia; Quercus ilex; tree growth; tree mortality; vegetation stabilizing processes

Seasonality of monoterpene emission potentials in Quercus ilex and Pinus pinea: Implications for regional VOC emissions modeling - KEENAN, Trevor; Niinemets, Ülo; Sabaté, Santi; Gracia, Carlos; Penuelas, Josep (Journal of Geophysical Research: Atmospheres, 2009)
VOC emissions from terrestrial ecosystems provide one of the principal controls over oxidative photochemistry in the lower atmosphere and the resulting air pollution. Such atmospheric processes have strong seasonal cycles. Although similar seasonal cycles in VOC emissions from terrestrial ecosystems have been reported, regional emissions inventories generally omit the effect of seasonality on emissions. We compiled measurement data on seasonal variations in monoterpene emissions potentials for two evergreen species (Quercus ilex and Pinus pinea) and used these data to construct two contrasting seasonal response functions for the inclusion in monoterpene emission models. We included these responses in the Niinemets et al. model and compared simulation results to those of the MEGAN model, both with and without its predicted seasonality. The effect of seasonality on regional monoterpene emissions inventories for European Mediterranean forests dominated by these species was tested for both models, using the GOTILWA+ biosphere model platform. The consideration of seasonality in the Niinemets et al. model reduced total estimated annual monoterpene emissions by up to 65% in some regions, with largest reductions at lower latitudes. The MEGAN model demonstrated a much weaker seasonal response than that in the Niinemets et al. model, and did not capture the between species seasonality differences found in this study. Results suggest that previous regional model inventories based on one fixed emission factor likely overestimate regional emissions, and species-specific expressions of seasonality may be necessary. The consideration of seasonality both largely reduces monoterpene emissions estimates, and changes their expected seasonal distribution.
Keywords: Holm oak; Italian stone pine; Models; regional inventory; Seasonality; VOC emissions

Sustained accumulation of methyl salicylate alters antioxidant protection and reduces tolerance of holm oak to heat stress - Llusia, Joan; Penuelas, Josep; Munné-Bosch, Sergi (Physiologia Plantarum, 2005)
Methyl salicylate (MeSA) is thought to have a major role in biotic and abiotic stresses by acting as a signal to trigger the oxidative burst, which is needed to activate gene expression in plant stress responses. To assess the potential effects of sustained foliar accumulation of MeSA on plant stress tolerance, the extent of photo- and antioxidant protection, lipid peroxidation and visual leaf area damage were evaluated in MeSA-treated (c. 60 nl l−1 in air) and control holm oak (Quercus ilex L.) plants exposed to heat stress. Control plants showed an increase in foliar MeSA levels up to 1.8 nmol [gDW]−1 as temperature increased and they displayed tolerance to temperatures as high as 45°C, which might be attributed, at least in part, to enhanced xanthophyll de-epoxidation and increases in ascorbate and α-tocopherol. MeSA-treated plants showed a sustained foliar accumulation of this compound, with values ranging from 10 to 23 nmol [gDW]−1 throughout the experiment. These plants showed lower ascorbate and tocopherol levels and higher oxidative damage at 50°C than controls, as indicated by enhanced malondialdehyde levels and leaf area damage and lower maximum efficiency of PSII photochemistry (Fv/Fm ratio). These results demonstrate that a sustained foliar accumulation of MeSA is detrimental to plant function and that it can reduce thermotolerance in holm oak by altering antioxidant defences.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: antioxidant protection (voyant); foliar MeSA accumulation; heat stress; Holm oak; methyl salicylate